Autocontrole de conhecimento de performance (CP) e de conhecimento de resultados (CR) na aquisição de habilidades motoras - Auro Barreiros Freire (2017)
Studies have investigated the effects of self-control of knowledge of results and knowledge of performance in a isolated way. Results of these studies have demonstrated superior performance of self-controlled condition in both (KR and KP). The present study investigated the effect of simultaneous and isolated self-controlled of KR and KP in motor skills learning, as well as the strategies that drive practice context adequate to the learner needs. Seventy two participants (M=24.4 year-old, sd=3.5), novice in the task, performed the floating serve with aim to hit a bull-eye target placed on the floor in the opposite side of court. Six experimental groups were constituted following the available information (KP, KR, and KP or KR) and kind of feedback (self-controlled or yoked) in three distinct experiments: In each experiment, self-controlled and yoked groups were compared, being provided KP in the first, KR in the second and KP and KR in the third study. The experiments consisted of acquisition phase with 200 trials and tests (after-test and retention) with 10 trials. Average score in the target and movement pattern score were utilized as performance measures. Experiments results showed that all groups presented similar performance in target and groups that receive self-controlled KP presented superior performance in movement pattern score. It was verified that self-controlled groups used cognitive strategies from performance goals setting in relation to the target as well as to the movement pattern. Still, they also used meta-cognitive strategies to monitoring, evaluating and changing the goals of cognitive strategies in order to become practice context more adequate to individual needs.